Quercetin Shows the Pharmacological Activity to Simultaneously Downregulate the Inflammatory and Fibrotic Responses to Tissue Injury in Association with its Ability to Target Multi-Kinases - Song, Ju-Yong; Do Vinh Truong; Yang, Beom-Seok (KARGER, 2018)
Aim: Previous studies have suggested that quercetin is effective for treating diverse chronic disorders including organ fibrosis and airway and cardiovascular disorders. To access the pharmacological background for its broad efficacy, we examined the ability of quercetin to modulate the inflammatory and fibrotic responses associated with organ injury that commonly underlie the pathogenesis of those disorders. Methods: A cutaneous wound model on rabbit ear was used for in vivo study. Quercetin was topically applied to the wounds, and the number of macrophages and myofibroblasts and the size of the hypertrophic scar formed were estimated. An in vitro study examined the ability of quercetin to inhibit cell-signaling pathways that activate RAW264.7 macrophages and primary dermal fibroblasts and the tyrosine kinase activity of discoidin domain receptor 2. Results: Quercetin reduced the population of macrophages and myofibroblasts and the scar formation in cutaneous wound healing. Quercetin suppressed the signaling pathways activating RAW264.7 macrophages and dermal fibroblasts, which is associated with its inhibition of multiple tyrosine kinases to regulate the pathways. This pharmacological activity of quercetin to simultaneously inhibit the inflammatory and fibrotic responses upon tissue damage by targeting multi-kinases could be the action mechanism to support its broad efficacy for various chronic disorders. (C) 2018 S. Karger AG, Basel
Keywords: DISCOIDIN DOMAIN RECEPTOR-2; PROTEIN-TYROSINE KINASE; FOCAL ADHESION KINASE; SRC FAMILY KINASES; SIGNALING COMPLEX-FORMATION; ANTIINFLAMMATORY ACTIVITY; MESENCHYMAL TRANSITION; HUMAN NEUTROPHILS; ALDOSE REDUCTASE; CELL-MIGRATION